Malay ESL students’ difficulties in using English prepositions - Loi, Chek Kim; Songyut Akkakoson; Mehmet Cem Odacıoğlu; Norazah Mohd Suki; Henry Bating (International Journal of Languages, Literature and Linguistics, 2017)
The study attempts to undertake an error analysis of prepositions employed in the written work of Form 4 Malay ESL (English as a Second Language) students in Malaysia. The error analysis was undertaken using Richards’s (1974) framework of intralingual and interlingual errors and Bennett’s (1975) framework in identifying prepositional concepts found in the sample. The study first identified common prepositional errors in the written texts of 150 student participants. It then measured the relative intensities of these errors and found out possible causes for the occurrences of these errors. In this study, one significant finding is that among the nine concepts of prepositions examined, the participant students tended to make the most number of errors in the use of prepositions of time and place. The present study has pedagogical implications in teaching English prepositions to Malay ESL students.